A New Nonrelativistic Atomic Energy Spectrum of Energy Dependent Potential for Heavy Quarkouniom in Noncommutative Spaces and Phases Symmetries - Abdelmadjid Maireche (Журнал нано- та електронної фізики)
The main objective of this search work is to study a three dimensional space-phase modified Schrödinger equation with energy dependent potential plus three terms: , and is carried out. Together with the Boopp’s shift method and standard perturbation theory the new energy spectra shown to be dependent with new atomic quantum in the non-commutative three dimensional real spaces and phases symmetries (NC-3D: RSP) and we have also constructed the corresponding deformed noncommutative Hamiltonian for studied potential.